Strategi pengembangan industri rotan di kota palu sulawesi tengah studi kasus cv. Bone layana jaya - Rasdiyanah, .; Umar, Syukur; Sustri, . (Jurnal Warta Rimba, 2018)
Forest product in Indonesia especially in Central Sulawesi has a very important role in the effort of  national and regional development evenly, because it will improve the state income and also provide job opportunity. In case that rattan is the most important nonwood forest product in Indonesia and one of superior commodity of Central Sulawesi. Since seventies, Indonesia has known as the biggest exporter country of rattan raw  material in the world. The aim of the research was to find out the development strategy of rattan industry in Palu City of Central Sulawesi, case study of CV. Bone Layana Jaya. The reasearch was conducted in Bone Layana Jaya Palu Central Suawesi Province, it was from March up to the month of May 2015. The analysis method that used in the resaerch was SWOT analysis with 2 strategy formulas, they were Internal and External (IE) strategies then SWOT matrix could be decided. Based on Grand Matrix  Internal Strategic Factors Analysis Summary (IFAS) was on the point of 3.49 and analysis  External Strategic Factors Analysis Summary (EFAS) was on the point of 3.27, the obtained rate on Matrix SWOT showed the strategy used in the industry more emphasized to WO (Weaknesse-oppurtunities) strategy, it was Government Contribution in Industry Development.  Therefore, in the curve of  Grand Matrix Strategy, the position of  enterprise industry was on quadrant I, it showed that the industry faced the environment that relatively had a bigger opportunity to handle its weakness.Keywords : Sulawesi Forest (Rattan),  Internal/External Strategy, SWOT matrix.